2014
DOI: 10.1136/gutjnl-2013-305965
|View full text |Cite
|
Sign up to set email alerts
|

Increased colonic bile acid exposure: a relevant factor for symptoms and treatment in IBS

Abstract: Increased colonic bile acid exposure influences bowel habit and colonic transit time in patients with IBS. A high response rate to open label treatment with colestipol supports this, but placebo-controlled studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
170
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(189 citation statements)
references
References 67 publications
12
170
0
7
Order By: Relevance
“…Another limitation is that we did not assess symptom severity and its relationship with BAD, although a recent study has suggested that perceived symptom severity is not linked to 75 SeHCAT retention values. 17 Nevertheless, as a low 75 SeHCAT retention test value is characterised by having more frequent stools, and accelerated colonic transit time, future studies in patients presenting with D-IBS type symptoms may wish to explore whether quantifying stool frequency or consistency can be used as a predictive tool to diagnose idiopathic BAD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another limitation is that we did not assess symptom severity and its relationship with BAD, although a recent study has suggested that perceived symptom severity is not linked to 75 SeHCAT retention values. 17 Nevertheless, as a low 75 SeHCAT retention test value is characterised by having more frequent stools, and accelerated colonic transit time, future studies in patients presenting with D-IBS type symptoms may wish to explore whether quantifying stool frequency or consistency can be used as a predictive tool to diagnose idiopathic BAD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have demonstrated a beneficial response to open treatment, particularly in those with moderate to severe BAD. 17,23 A systematic review noted that response to colestyramine occurred in 96% of patients with 75 SeHCAT retention <5%, 80% with 75 SeHCAT retention <10%, and 70% with 75 SeHCAT retention <15%. 23 In our study, of those that had BAD, 28.6% were mild, 28.6% moderate and 42.8% severe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiene el mismo mecanismo de acción que la colestiramina y es una alternativa para aquellos pacientes que no toleren dicha medicación, no es absorbido en la circulación sistémica por lo tanto no requiere ajuste en falla renal o enfermedad hepática crónica; en pacientes con síndrome de intestino irritable y mala-absorción de AB se ha demostrado una mejoría sintomática global superior al 50% evaluada entre la semana 5 y 8 de terapia (48,49)No se han realizados estudios del uso del colestipol como única terapia (47).…”
Section: -Colestipolunclassified